Disclosure of wrongdoings and protection of employee whistleblower under the Malaysian and Nigerian law - Ali Mohamed, Ashgar Ali; Ahmad, Abubakar Aminu; Sardar Baig, Farheen Baig (UPM Press, 2015)
This article is a doctrinal legal research that employs comparative approach to analyse and explore employee whistleblower protection in Malaysia and Nigeria and under the common law as well. Employee whistleblowers who reported the misconduct of a fellow employee or superior within their organisation frequently face reprisal or retaliation, sometimes at the hands of the employer or the group which they have accused. While the article considered related instruments in the two countries under consideration in the analysis, the focus is on the Whistleblower Protection Act 2010 (WPA, 2010) and the Whistleblower Protection Bill 2011 (2011 Bill) in Malaysia and Nigeria, respectively. The article finds that the bulk of the present regime of whistleblower protection in Malaysia is contained in WPA 2010. The common law applies subject to the Act and other restrictions under the legal system of the country. In the case of Nigeria, on the other hand, as the 2011 Bill is still pending, the common law applies generally in guiding whistleblower protection in the country. The article further finds that the concept of whistleblowing is wider in common law than under the WPA 2010 in Malaysia or the 2011 Bill in Nigeria. The conclusion of the article is that while legislation is desirable for the promotion of whistleblower protection in the countries under consideration to accord protection against the fluid position of common law, the legislation should not be unduly used to limit the scope of the protection such as in terms of defining the authorities to whom the disclosure is to be made as suggested by both the WPA 2010 and the 2011 Bill and classification of persons that can make disclosure as in the 2011 Bill and which is not in line with the modern trends in whistleblowers protection.